Editorial: Volume 1 - Issue 1 - Cihan Cobanoglu; Serdar Ongan (Journal of Global Business Insights, 2016)
The National Academies defines interdisciplinary research as “a mode of research by teams or individuals that integrates information, data, techniques, tools, perspectives, concepts, and/or theories from two or more disciplines or bodies of specialized knowledge to advance fundamental understanding or to solve problems whose solutions are beyond the scope of a single discipline or area of research practice.” The fields of business and economics are very suitable for interdisciplinary research. For this reason, we decided to develop and publish an international double blind peer reviewed journal - International Interdisciplinary Business- Economics Advancement (IIBA) Journal - to feature business and economics research that spans more than one discipline. The IIBA Journal aims to publish new ideas, research and results concerning all aspects of Business and Economics, and to discuss the practical challenges encountered in the field as well as the solutions adopted. Hence, it will be a platform where numerous disciplines converge. For this reason, we invite scholars from different academic disciplines to collaborate with scholars from other disciplines, tackle issues to solve current and future problems, contribute to the body of knowledge and share their views and research findings. IIBA Journal also welcomes any conceptual papers in addition to contributions towards theory testing and development which will help future empirical studies. It is with a great pleasure that we welcome you to the inaugural issue of the IIBA Journal. This issue presents five excellent contributions. The first paper by Jeetesh Kumar and Kashif Hussain assesses the factors for medical tourism destination selection from medical tourist’s perspective and to determine the satisfaction level of medical tourists in Malaysia. In the second paper, Philipp E. Leffler furthers the argument that economic globalization began in the early 16thcentury with the birth and expansion of inter-continental trade between the New World, Asia, and Europe; opposing the theory about birth of Globalization in the early 20th century. On another dimension, the third paper by Rui V. da Silva and Natalia Teixeira explains the institutional and structural conditions in an economy as key drivers of country competitiveness by taking southern European economies as a case. The fourth paper by Daniel H. Lam dissects the leading university education policy in China by conducting a qualitative research to explore if the policy implementation is producing the desirable results for the students and the lecturers. Last but not least, the fifth paper by Suleyman N. Oz, Ali Ihtiyar, Fauziah S. Ahmad and Faizan Ali presents a comprehensive and conceptual framework on key factors of intercultural interaction influencing customer satisfaction within the tourism industry. Please provide feedback for the articles that are published in IIBA Journal. I also invite you to submit an article for IIBA Journal.